The Role of Marketing Campaigns Through Social Media and Perceived Usefulness on Purchase Intention of Electric Vehicle - Hendra, Hendra; Fadhilah, Nurul; Yani, Indri; Violin, Vivid; Apramilda, Riesna; Kushariyadi, Kushariyadi (Malikussaleh University, Aceh, Indonesia, 2025)
This study investigates consumers' perceptions of the utility of electric vehicles and the effectiveness of social media marketing efforts on EV purchase intentions. Marketers and lawmakers must understand the drivers of electric vehicle adoption in light of increasing concerns about environmental sustainability and technological development. The research strategy adopted for the study is a quantitative approach based on a survey. A cross-section of social media users exposed to advertisements regarding electric vehicles were surveyed. The perceived utility of EVs includes environmental advantages, cost savings, and performance measured by the questionnaire, as well as the exposure to social media marketing activities and intention to purchase. Regression analysis is used as the analytical approach to finding how the variables relate. Therefore, a positive relationship exists between social media marketing efforts and perceived usefulness intending to purchase. In instances where consumers are subjected to persuasive social media advertisements describing the benefits of EVs, and when they view an EV as practical, they show a greater tendency to express an intention to buy. The practical implications of this study will help marketers devise social media ads that successfully promote electric vehicle adoption; it also adds to the literature on sustainable consumerism. This study's results will benefit politicians who want to encourage the switch toward electric mobility.